Characterizing the spatio-temporal threats, conservation hotspots and conservation gaps for the most extinction-prone bird family (Aves: Rallidae). Issue 9 (8th September 2021) - Lévêque, Lucile; Buettel, Jessie C.; Carver, Scott; Brook, Barry W.
Abstract : With thousands of vertebrate species now threatened with extinction, there is an urgent need to understand and mitigate the causes of wildlife collapse. Rails (Aves: Rallidae), being the most extinction-prone bird family globally, and with one-third of extant rail species now threatened or near threatened, are an emphatic case in point. Here, we undertook a global synthesis of the temporal and spatial threat patterns for Rallidae and determined conservation priorities and gaps. We found two key pathways in the threat pattern for rails. One follows the same trajectory as extinct rails, where island endemic and flightless rails are most threatened, mainly due to invasive predators. The second, created by the diversification of anthropogenic activities, involves continental rails, threatened mainly by agriculture, natural system modifications, and residential and commercial development. Indonesia, the USA, the United Kingdom, New Zealand and Cuba were the priority countries identified by our framework incorporating species' uniqueness and the level of endangerment, but also among the countries that lack conservation actions the most. Future efforts should predominantly target improvements in ecosystem protection and management, as well as ongoing research and monitoring. Forecasting the impacts of climate change on island endemic rails will be particularly valuable to protect rails.